2010
DOI: 10.1007/s10209-010-0204-x
|View full text |Cite
|
Sign up to set email alerts
|

The design-by-adaptation approach to universal access: learning from videogame technology

Abstract: This paper proposes an alternative approach to the design of universally accessible interfaces to that provided by formal design frameworks applied ab initio to the development of new software. This approach, design-by-adaptation, involves the transfer of interface technology and/or design principles from one application domain to another, in situations where the recipient domain is similar to the host domain in terms of modelled systems, tasks and users. Using the example of interaction in 3D virtual environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Researchers are looking for an efficient and accessible wayfinding system that can be used both indoors and outdoors [5][6][7][8][9], but the time comes where psychological feelings should be considered as well. The hierarchy of walking needs a mention of pleasure as a higher-level need [30], and this theory provides inspiration for further studies which can be referred to in Section 4.…”
Section: Wayfindingmentioning
confidence: 99%
“…Researchers are looking for an efficient and accessible wayfinding system that can be used both indoors and outdoors [5][6][7][8][9], but the time comes where psychological feelings should be considered as well. The hierarchy of walking needs a mention of pleasure as a higher-level need [30], and this theory provides inspiration for further studies which can be referred to in Section 4.…”
Section: Wayfindingmentioning
confidence: 99%
“…The concern is that these training simulators, whether military warfare, crisis management, air traffic control or medical surgery, are serious businesses that may not have any resemblance to the competition, excitement and fun of games. Nonetheless, as Shepherd and Bleasdale-Shepherd [97] show, potential gains can be achieved by transferring knowledge from video games to other domains, e.g., virtual geographic environments, via design-byadaptation. Other research has shown that the transfer of knowledge from an aerospace application to cruise control in cars has potentially compromised safety [98].…”
Section: Transfer Of New Knowledgementioning
confidence: 99%
“…With the advances in information technology (IT) , its increasing impact on humans and society and its requirements increasingly formed by a domain [4], there has been an expanding need to spread knowledge from domain to domain. This need is not least in the area of human-computer interaction, and we have seen examples involving design [5] and evaluation [6]. Transfer of knowledge appears in miscellaneous instantiations and can be of varying degrees.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge can be adapted to new settings, technologies can be adopted by companies, and in some cases the targeting context is so different from the original one that it calls for knowledge transformation. Shepherd and Bleasdale-Shepherd [5] explicate a framework, design-by-adaption, with a case study that shows how the design of a video game can be transferred to visualization of geographical data. Heuristics evaluation is an expert review method proposed in the early nineties to evaluate the usability of software systems [7], and has been applied in many domains, sometimes unchanged but sometimes altered.…”
Section: Introductionmentioning
confidence: 99%